2019
DOI: 10.3747/co.26.4479
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Image-Guided Neoadjuvant Ablative Single-Dose Radiation, then Lumpectomy, for Early Breast Cancer: The Signal Prospective Single-Arm Trial of Single-Dose Radiation Therapy

Abstract: Background and Purpose Adjuvant whole-breast irradiation after breast-conserving surgery, typically delivered over several weeks, is the traditional standard of care for low-risk breast cancer. More recently, hypofractionated, partial-breast irradiation has increasingly become established. Neoadjuvant single-fraction radiotherapy (rt) is an uncommon approach wherein the unresected lesion is irradiated preoperatively in a single fraction. We developed the signal (Stereotactic Image-Guided Neoadjuvant Ablative R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Accelerated partial breast irradiation (APBI) is an alternative to whole breast irradiation after lumpectomy for low risk breast cancer patients selected according to several international guidelines [1][2][3][4][5][6]. There is a tendency to reduce the number of treatment fractions for APBI from ten to five, or even down to single fraction treatments [7][8][9][10][11][12][13][14]. Hypofractionation has the advantage of convenience both for the patient and the radiotherapy facility, but could create challenges for the treatment delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Accelerated partial breast irradiation (APBI) is an alternative to whole breast irradiation after lumpectomy for low risk breast cancer patients selected according to several international guidelines [1][2][3][4][5][6]. There is a tendency to reduce the number of treatment fractions for APBI from ten to five, or even down to single fraction treatments [7][8][9][10][11][12][13][14]. Hypofractionation has the advantage of convenience both for the patient and the radiotherapy facility, but could create challenges for the treatment delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In the neoadjuvant setting, the use of T1-weighted fatsuppressed contrast-enhanced MRI is recommended for optimal tumour and tumour spiculae visualization, because differences in contrast uptake provide a clear distinction between tumour and glandular breast tissue (Figure 3) (35)(36)(37)(38). Additionally, T2weighted images might aid in the differentiation between tumour and postbiopsy changes (35).…”
Section: Choice Of Mr Image Contrastmentioning
confidence: 99%
“…Several publications have reported on neoadjuvant MR-guided PBI on a conventional linac including favourable toxicity profiles (35,37,85). However, no patients have yet been treated with neoadjuvant PBI on a hybrid machine.…”
Section: First Clinical Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…This treatment paradigm also provides an opportunity to test biomarkers for radiation response. Two single-institution studies that used 15Gy-21Gy SFRT have reported favorable early cosmetic outcomes (31,32). MRI-guided RT could potentially contribute to this evolving paradigm by reducing PTV margins and thereby treatment volumes (clinical trials.gov: NCT03863301).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%